EKSISTENSI PEREMPUAN DALAM SENTRA INDUSTRI KOPI DI NAGARI KOTO TUO KECAMATAN SUNGAI TARAB: PERSPEKTIF FEMINISME LIBERAL - Rahmah Husna Yana; Triyanto Triyanto; Rachmatika Lestari (Jurnal Society : Pengamat Perubahan Sosial, 2026)
Abstract*Nagari Koto Tuo, Sungai Tarab District, Tanah Datar Regency is one of the largest ground coffee industrial centers in West Sumatra, as nearly 80% of the population depends economically on ground coffee production, with women serving as the primary driving force. This study aims to analyze women’s existence within the coffee industry center and their position in Minangkabau customary law through the lens of liberal feminism. A descriptive qualitative method was employed, utilizing in-depth interviews and field observation. The findings reveal that all coffee production activities—from bean processing and roasting to product packaging—are carried out entirely by women. This involvement has led to enhanced social status, financial independence, and community recognition, while simultaneously transforming traditional gender perceptions. Within the analytical framework of liberal feminism, the role of women in Nagari Koto Tuo reflects a harmony between economic rights equality and the matrilineal values of Minangkabau customary tradition.